Ribā and contemporary Islamic banking: a Sharī’ah perspective on debt-credit relationships - Sultan, Ambreen; Mat Ghani, Gairuzazmi (International Research Centre of Islamic Economics and Finance (IRCIEF-UIS), 2025)
This paper attempts to revisit the concept of ribā in light of the definition provided by famous Muslim jurist Imām Muhammad al-Sarakhsī (d. 1096) and explains it in detail. It shows that the concept of ribā is more than mere ‘interest’ and it includes the prohibition of fundamental monetary debtor-creditor relationship which is the foundation stone of contemporary capitalist banking and finance. These insights carry profound implications for contracts being utilized by Islamic banks to form relationships with their clients. Selected contracts are critically analyzed in light of the definition of ribā. It is shown that after modification of originals by Sharī’ah scholars, these contracts boiled down to the same basic relationship of monetary debtor-creditor, which is unbreakable in the sense that capitalist money by its nature is nothing more than a promise to pay monetized through debtor-creditor relationships in the economy. The paper concludes that to achieve the objectives of Sharī’ah especially the objective of distributive justice, there is an urgent need to revisit and develop an equitable monetary system in line with the guidelines of Sharī’ah.